2005
DOI: 10.1093/intqhc/mzi061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating claims-based indicators of the intensity of end-of-life cancer care

Abstract: The usefulness of these measures will depend on whether the concept of intensity of care near death can be further validated as an acceptable and important quality issue among patients, their families, health care providers, and other stakeholders in oncology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
344
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 343 publications
(366 citation statements)
references
References 19 publications
13
344
5
4
Order By: Relevance
“…Policy implications some of the outcomes described in this study have been suggested as valid indicators for evaluating the quality of end-of-life care (Earle et al 2003(Earle et al , 2004(Earle et al , 2005. using administrative data in this way is consistent with a previously published quality framework for palliative and end-of-life care (stewart et al 1999).…”
Section: Other Findings From the Literaturesupporting
confidence: 86%
“…Policy implications some of the outcomes described in this study have been suggested as valid indicators for evaluating the quality of end-of-life care (Earle et al 2003(Earle et al , 2004(Earle et al , 2005. using administrative data in this way is consistent with a previously published quality framework for palliative and end-of-life care (stewart et al 1999).…”
Section: Other Findings From the Literaturesupporting
confidence: 86%
“…In research on claims-based measurement of cancer treatment quality, Earle et al define the 10th percentile as the benchmark for health care systems to set as a goal. 19 In their work evaluating the intensity of end-of-life cancer care, for example, this meant that hospitals would be providing appropriate-intensity care if less than 2% of patients started a new chemotherapy regimen in the last 30 days of life. We report the 25th percentile for each measure in Table 2 as a conservative initial benchmark for clinicians and health systems to work toward.…”
Section: Discussionmentioning
confidence: 99%
“…Not all aggressive care at the end of life is inappropriate and the ''right'' rates of the measures are not zero. Yet, these measures are well suited for comparing systems of care, 34 and recent data suggest that they provide comparable information to measures collected from medical record abstractions, collected either prospectively or retrospectively. 35,36 Moreover, some have questioned the validity of retrospective studies of end-of-life care for cancer patients because it is not always possible to identify the point at which physicians perceive patients' terminal status.…”
Section: Discussionmentioning
confidence: 99%